COMPARISON OF LENGTH, MORPHOLOGICAL WEIGHT OF BELANAK FISH (Mungilidae) IN THE FLOW ECOSISTEM OF THE UJUNG KULON-PANDEGLANG NATIONAL PARK, BANTEN AND THE FLOW ECOSISTEM OF PANJANG ISLAND, BATAM City - Setianingsih, Indri; Aulia Istiqomah, Dian; Budiarti Utami Putri, Luckita (Journal of Natural Sciences and Learning, 2023)
Habitat affects growth and can even affect fish morphology. Environmental factors also affect the weight, length, and morphology of fish, especially mullets. The aim of the study was to compare the weight, length and morphology of mullets in the Ujumg Kulon-Pandeglang aquatic ecosystem, Banten and Panjang Island, Batam city.